Collaborative Governance Dinas Sosial Provinsi Riau dalam Menangani Penyandang Masalah Kesejahteraan Sosial (PMKS) - Nadiya Wanti Anggrain; Dadang Mashur (Pencerah, 2022)
Abandoned Children are one of the most widely handled types of People with Social Welfare Problems in Riau Province. From year to year the population of abandoned children in Riau Province is increasing marked by the number of children who drop out of school, children who do not have parents, and children who are discarded by their parentS. Therefore, there is a collaboration from related agencies to deal with the high population of displaced children in Riau Province. In the collaboration process, there are still some obstacles that make the handling of abandoned children not run optimally. This research aims to find out collaborative governance by the Riau Provincial Social Service in dealing with the high population of displaced children. The concept of theory that researchers use is collaborative governance theory by Ansell and Gash with five indicators, namely face to face dialogue, trust building, commitment to process, share understanding, intermediate outcome. Research uses qualitative research methods with data collection techniques based on interviews, observations, and documentation. The results of the research found are collaborative governance has been implemented but not optimally, because on three indicators, namely the faSce to face dialogue indicator, trust building, and commitement to process that has not been fully implemented between the Riau Provincial Social Service and other stakeholders. Other obstacles faced in this collaboration process are the lack of quality and quantity of social workers, inadequate facilities and infrastructure, and the lack of budget allocation in dealing with displaced children